Antibiotic prescribing in neonatal sepsis: an Australian nationwide survey. Issue 1 (18th March 2020) - McMullan, Brendan; Cooper, Celia; Spotswood, Naomi; James, Rodney; Jones, Cheryl; Konecny, Pamela; Blyth, Christopher; Karen, Thursky
Abstract : Objective: To evaluate quality and variation in antibiotic prescribing for neonatal sepsis. Design: We analysed prescribing in hospitalised neonates using the National Antimicrobial Prescribing Survey in Australian neonates from 1 January 2014 to 31 December 2018. Setting: Data from antibiotic point prevalence surveys performed in hospitals, ranging from rural hospitals to tertiary paediatric and maternity hospitals within Australia. Patients: Admitted neonates <28 days of age from participating hospitals. Main outcome measures: Variation and appropriateness in prescribing for neonatal sepsis and variation in dosing for gentamicin and benzylpenicillin across hospitals. Results: A total of 415 prescriptions among 214 neonates from 39 different hospitals were included. The majority of prescriptions (342, 82.4%) were for neonates <7 days of age. The most commonly prescribed antibiotics were gentamicin and benzylpenicillin, with 323 (77.8%) prescriptions. Dosing variability was substantial, with doses ranging from 2 to 8 mg/kg for gentamicin (median 5 mg/kg, IQR 4–5) and from 45 to 72 mg/kg for benzylpenicillin (median 60 mg/kg, IQR 50–60), although only 13 (3.2%) and 19 (4.6%) prescriptions were locally assessed as inappropriate or non-compliant with guidelines, respectively. At time of audit, 22% of antibiotics had been given for more than 48 hours and 9% more than 72 hours, although microbiologically confirmed infection was documented in only nine (4.2%) neonates. Conclusions: Prescribing for neonatal sepsis was dominated by use of benzylpenicillin and gentamicin with substantial variation in dosing. A small minority had culture-confirmed infection. Efforts to standardise antibiotic dosing and duration for suspected neonatal sepsis are recommended.